Teledentistry: Limitation and Challenges - Nadia Sultana Shuborna; Sultana Sadia Islam; Shah Saif Jahan; Ehsanul Hoque Apu; Osama Bin Noor; Mohammad Tawfique Hossain Chowdhury Hossain Chowdhury (Update Dental College, 2021)
Dentistry is the top listed most risky jobs in this pandemic Covid 19 situation, as dentist contain close face-to-face contact with the patients which increase the potential transmission of the (SARS)-CoV-2 virus from human to human through direct contact via oro-pharyngeal droplets and indirect contacts with fomites where dental professionals are highly vulnerable to get infected from the coronavirus. Thus, dental practice has mostly been suspended during this period. Teledentistry introduces a novel solution to resume dental practice by providing dental treatment, guidance, and education through teleconsultation, telediagnosis and telemonitoring through Information Technology (IT) instead of direct contact with patients. But there are some major challenges like lack of government initiatives, compensation strategy, legal issues, technical base, co-ordination among doctors, along with patients' co-operation and limitations in telediagnosis. This technical note highlighted these limitations and challenges to make a concern to the dentist as at least teledentistry can accompaniment the existing threaten dental system during this living pandemic. Update Dent. Coll. j: 2021; 11(2): 1-3